Why Environmental Pollution Remains Unresolved Despite Efforts to Mitigate It? - Moniruzzaman (DIROSAT: Journal of Education, Social Sciences & Humanities, 2025)
Environmental pollution remains a persistent global challenge despite extensive efforts to mitigate its effects. This ongoing issue is driven by multiple factors, including industrialization, technological limitations, political barriers, and a lack of public awareness. Industrial activities continue to be the primary source of pollution, significantly degrading air, water, and soil quality (Jones, 2019). While technological advancements have introduced pollution control mechanisms, high costs and inefficiencies limit their widespread adoption, particularly in developing nations (International Energy Agency, 2021). Political and regulatory challenges, such as weak enforcement and regulatory capture by powerful industrial lobbies, further hinder effective pollution management (Smith, 2022; Miller & Davis, 2020). Additionally, the global nature of pollution necessitates international cooperation, but geopolitical interests and economic priorities often undermine international agreements like the Paris Agreement and the Kyoto Protocol (United Nations, 2015; UNEP, 2018). Compounding these issues is a general lack of public awareness and engagement, which weakens the impact of grassroots movements and the support for environmental policies (McKenzie-Mohr, 2011). As pollution levels rise, increasing public consciousness through direct experiences and media coverage becomes essential to drive collective action (Haines et al., 2006). This study concludes that a holistic approach, encompassing industrial reform, technological innovation, strong political will, and enhanced public awareness, is crucial for effectively addressing and mitigating the global threat of environmental pollution.